A KPI based study on the scope and quality of sustainability reporting by the DAX30 companies - Joris Greiwe; Avo Schönbohm (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2011)
This paper analyses the scope and the quality of the sustainability reporting of the DAX30 companies with the help of comparable Key Performance Indicators (KPIs) and a presentation of the general characteristics of the published reports with focus on the topics sustainability and sustainable actions. Whereas other recent studies have concentrated on more general information like the number of published reports, their frequency as well as the number of external audited reports, a research gap exists in the identification of the priorities and weighting of the sustainability perspectives within the communication to the companies' stakeholders. The empirical analysis suggests that the DAX30 companies recognize the increasing importance of sustainability in their communication with the stakeholders. Differences were found in the reporting of the companies' sustainable actions. Possible reasons for this could be the different importance attached to the topic within the companies and their surroundings, their business activities, the required information by their different stakeholders but also the degree of performance of sustainability. – – Die vorliegende Arbeit analysiert den Umfang und die Qualität der Nachhaltigkeitsberichterstattung der DAX30-Unternehmen mit Hilfe von definierten Key Performance Indicators (KPI) und stellt die allgemeinen Merkmale der veröffentlichten Berichte mit Fokus auf das Thema Nachhaltigkeit und nachhaltiges Handeln dar. Während sich andere Studien auf allgemeine Informationen wie die Anzahl der veröffentlichten Berichte, deren Veröffentlichungsfrequenz und die Anzahl der externen geprüften Berichte konzentrieren, wurde eine Lücke in der Identifizierung der Prioritäten und der Gewichtung der Nachhaltigkeitsperspektiven identifiziert und mit dieser Studie geschlossen. Die Ergebnisse der empirischen Analyse verdeutlichten, dass die DAX30-Unternehmen die zunehmende Bedeutung von Nachhaltigkeitsaspekten und deren Kommunikation mit den unterschiedlichen Interessensgruppen erkannt haben. Bei der Berichterstattung über das nachhaltige Handeln wurden erheblich Unterschiede identifiziert. Als Gründe hierfür können die unterschiedlichen Bedeutung des Themas im Unternehmen und in ihrer Umgebung, die Geschäftstätigkeit, die Differenz der geforderten Informationen durch die unterschiedlichen Interessensgruppen als auch die erbrachte Leistung im Bereich Nachhaltigkeit des Unternehmens herangezogen werden.
Keywords: 650